2007
DOI: 10.4028/www.scientific.net/kem.345-346.653
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Mg-Al-Ca-Sm Alloys at High Temperature

Abstract: The aims of this research are to investigate the effect of Sm addition in Mg-Al-Ca alloys on microstructure and mechanical properties. Sm addition to Mg-5Al-3Ca based alloys results in the change from dendritic to equiaxed grain morphorlogy and formation of Al-Sm rich itermetallic compounds at grain boundary and α-Mg matrix. And these Al-Sm rich intermetallic compounds were dispersed homogeously and stabilized at high temperature. And maximum yield and ultimate strength value was obtained at Mg-5Al-3Ca-2Sm all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…2b). In our recent papers [17], it was confirmed that the ␣-Mg matrix morphology was changed from dendritic to equiaxed grains with an increase in the addition of Sm from 1 wt% to 3 wt% due to the suppression of grain growth by the formation of homogeneous intermetallic compounds containing Sm at the ␣-Mg matrix and grain boundary. To observe the eutectic phase distribution, the specimens were tilted 70 • in the SEM chamber.…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…2b). In our recent papers [17], it was confirmed that the ␣-Mg matrix morphology was changed from dendritic to equiaxed grains with an increase in the addition of Sm from 1 wt% to 3 wt% due to the suppression of grain growth by the formation of homogeneous intermetallic compounds containing Sm at the ␣-Mg matrix and grain boundary. To observe the eutectic phase distribution, the specimens were tilted 70 • in the SEM chamber.…”
Section: Methodsmentioning
confidence: 74%
“…1a and b), the grey and bright contrast phases were observed. The grey and bright phases were identified with the (Mg, Al) 2 Ca eutectic phase [17] and Al-Sm-rich intermetallic compounds by EDS (Fig. 1c), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microstructure of as-cast alloys with Nd additons consists of -Mg matrix and eutectic phase and Nd containing intermetallic compounds. These eutectic phases and Nd containing intermetallic compounds with bright contrast were identified to (Mg, Al) 2 Ca phase 18,19) and Al-Nd rich intermetallic compound by SEM-EDS analysis, respectively. In microstructure of Nd containing alloys, Al-Nd rich intermetallic compounds were observed at both grain boundary and -Mg matrix.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the addition of Ca to Mg-Al alloys has been found to improve the mechanical properties. This is because the more stable Mg 2 Ca and/or Al 2 Ca Laves phase or (Al, Mg) 2 Ca phase are precipitated by an eutectic reaction along the grain boundaries during the solidification of Mg-Al-Ca alloys instead of the Al 12 Mg 17 phase [1][2][3]. Moreover, it is well known that the addition of rare earth (RE) elements is an effective way to improve the mechanical properties of magnesium alloys at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%